Candida Species-Dependent Release of IL-12 by Dendritic Cells Induces Different Levels of NK Cell Stimulation. (29th January 2020) - Marolda, Alessandra; Hünniger, Kerstin; Böttcher, Sarah; Vivas, Wolfgang; Löffler, Jürgen; Figge, Marc Thilo; Kurzai, Oliver
Abstract: Background: Candida albicans and Candida glabrata are the 2 most prevalent Candida species causing bloodstream infections. Patterns of innate immune activation triggered by the 2 fungi differ considerably. Methods: To analyze human natural killer (NK) cell activation by both species, we performed ex vivo whole-blood infection assays and confrontation assays with primary human NK cells. Results: C. albicans was a stronger activator for isolated human NK cells than C. glabrata . In contrast, activation of blood NK cells, characterized by an upregulated surface exposure of early activation antigen CD69 and death receptor ligand TRAIL, as well as interferon-γ (IFN-γ) secretion, was more pronounced during C. glabrata infection. NK cell activation in blood is mediated by humoral mediators released by other immune cells and does not depend on direct activation by fungal cells. Cross-talk between Candida- confronted monocyte-derived dendritic cells (moDC) and NK cells resulted in the same NK activation phenotype as NK cells in human blood. Blocking experiments and cytokine substitution identified interleukin-12 as a critical mediator in regulation of primary NK cells by moDC. Conclusions: Activation of human NK cells in response to Candida in human blood mainly occurs indirectly by mediators released from monocytic cells. Abstract : NK cells are integral part of antifungal immunity. Whereas Candida albicans is a stronger stimulus than Candida glabrata for human NK cells upon direct contact, only C. glabrata triggers strong indirect NK-cell activation in human blood via IL-12.